PENERAPAN BOUNDARY VALUE ANALYSIS PADA APLIKASI KEPEGAWAIAN LENKA EDUKASI - Fadil Firdian; Zainul Efendy; Liranti Rahmelina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research is motivated by an error in the data verification process that will be entered on the employee data form which consists of several fields including the place of birth and email fields so that the expected data does not match the data stored in the database. The purpose of this research is to determine the level of data accuracy and the success of the lenka edukasi staffing application running according to its function. The research method used is Black Box with Boundary Level Analysis technique. Where this method tests and analyzes the values entered in applications that have maximum and minimum value limits. Application testing is carried out on the employee data form which contains the employee registration page before carrying out further activities on the application. The selection of the employee data form is because the data on the form is related to other data in the application. The result of the research is the application of staffing lenka edukasi is able to process data with a success rate of 95.83%, so the application needs improvement so that it can run according to its function.